Characterization of the complete mitochondrial genome of the coral reef fish, Hemigymnus melapterus (Pisces: Labridae) and its phylogenetic implications. Issue 2 (3rd July 2019) - Yi, Murong; Gu, Sui; Luo, Zhisen; Lin, Hung-Du; Yan, Yunrong
Abstract: Hemigymnus melapterus belongs to the family Labridae, which inhabit in coastal and continental shelf waters. The entire mitochondrial genome of H. melapterus is 16, 527 base pairs (bp) in length and contained 13 protein-coding genes, two rRNA genes, and 22 tRNA genes. The overall base composition is 27.56% A, 25.58% T, 30.02% C, and 16.85% G, showing AT-rich feature (53.14%). Phylogenetic analysis based on 13 protein-coding genes shows the H. melapterus has the closest evolutionary relationship with Stethojulis strigiventer . This work provides valuable genome variation information, which will be useful for phylogenetic analysis and population genetics research.